Genetic variability among power athletes: The stronger vs. the faster - Ben-Zaken, S.; Eliakim, A.; Nemet, D.; Meckel, Y. (The Journal of Strength and Conditioning Research, 2019)
Athletic events can be divided into "aerobic-type events" or "anaerobic-type events" based on energy usage. Power, speed, and strength are also used to specify sports subtypes. Weightlifters (WLs), sprinters, and jumpers feature high-intensity efforts lasting a few seconds. However, their performance requires different proportions of power, speed, and strength. The aim of the current study was to examine genetic differences between subtypes of anaerobic athletes in 3 genetic variants: ACTN3 R577X, which is associated with muscle contractions; AGT Met235Thr which is associated with muscle growth; and PPARD T/C, which is associated with aerobic capacity. Seventy-one sprinters and jumpers (S/J), 54 WLs, and 86 controls participated in the study. Genomic DNA was extracted from peripheral blood using a standard protocol. Genotypes were determined using a TaqMan allelic discrimination assay. The ACTN3 RR genotype frequency was significantly higher among S/J (39.4%) compared with WLs (22.2%) and controls (18.6%). The AGT Thr-Thr genotype frequency was significantly higher among WLs (25.9%) compared with S/J (4.2%) and controls (12.8%). PPARD T294C genotype frequencies did not differ between groups. The results suggest that there may be a specific genetic makeup enabling an athlete to excel in speed-oriented events (sprints), rather than in strength-oriented events (weightlifting).